Phytochemical and Antinociceptive Investigations of Anemone coronaria Active Part Ameliorating Diabetic Neuropathy Pain - Raafat, Karim; El-Lakany, Abdalla (Planta Medica International Open, 2018)
Phytochemicals might offer economic therapies, which are an alternative especially for low-income developing countries. Anemone coronaria has been used extensively as antineuralgic and antirheumatic in the folk medicine of Lebanon. Thus, the aim of this study was to investigate the antinociceptive potential of A. coronaria and its active principles against diabetic-neuropathy pain in a mouse-model. The study also aimed to achieve a bio-guided fractionation and to isolate the most active principles in A. coronaria herb. Bio-guided fractionation used reversed phase-HPLC, and 1H and 13C NMR for the identification of the most active fraction of A. coronaria, which was rich in alkaloids. This isolated alkaloid rich fraction contained catalin (21.1%), thaliporphine (14.1%), and glaucine (compound 3) (63.4%). A. coronaria extract (50, 100, and 200 mg/kg), the isolated alkaloid rich fraction (70 mg/kg), and glaucine (25, 50, and 100 mg/kg) showed significant reduction in acute and subchronic hyperglycemia, with significant increase in glutathione and catalase levels, along with normalization of HbA1c and LPO levels (n=7 per group, p≤0.05). A. coronaria extract (50, 100, and 200 mg/kg), the isolated alkaloid rich fraction (70 mg/kg), and glaucine (25, 50, and 100 mg/kg) also showed significant antinociceptive amelioration in thermal hyperalgesia pain latencies utilizing hot plate and tail flick tests. The highest doses of A. coronaria extract (200 mg/kg), isolated alkaloid rich fraction (70 mg/kg), and glaucine (100 mg/kg) showed a significant elevation in mechanical allodynia pain thresholds using Von-Frey-filaments. The results revealed that A. coronaria herb along with its most active alkaloid rich fraction and constituent (glaucine) possessed significant antihyperglycemic and antinociceptive potentials. These findings may lead to a future use of A. coronaria in the management of diabetic-neuropathy pain.
Keywords: Anemone coronaria; Ranunculaceae; diabetic-neuropathy pain; glaucine; in vivo antioxidant; HbA1c